Community Engagement for Imam and Khatib Development in Nagari Muaro Aie, Kec Iv Bayang Utara - Purnama, Randi; Yanti, Yosi Marlinda (MARAWA: Jurnal Masyarakat Religius dan Berwawasan, 2022)
Categories to be a sermon and imam need to know about several pillars, conditions and others, so that when they be Friday sermon and imams, these things have been mastered as well as possible. The purpose teach is to understand the community so that when they be a sermon and imam, they look ┬áat the age category but many things need to be considered. The result from teach is community muaro aie be a sermon and imams. Because the purpose from teach is to understand be a semon and imams. To achieve the above objectives, the method used is Participatory Action Research (PAR). There are 3 main activities carried out, material giving, Practice preaching from the class, and Practice preaching from the pulpit. In this ministry, it is empirically proven that overseeing the training of priests and preachers can enhance the insight and knowledge of the people of Nagari Muaro Aie, Kec IV Bayang Utara. This service is intended to be an incentive to other people who are interested in engaging in religious activities in society.